Association of soluble suppression of tumorigenicity 2 protein with new-onset atrial fibrillation in patients with acute ST-segment elevation myocardial infarction undergoing primary PCI - Zhao, Ting-ting; Pan, Tian-jiao; Yang, Yi-bo; Pei, Xiao-yang; Wang, Yong (Frontiers in Cardiovascular Medicine, 2023)
Background Previous studies have indicated that the soluble suppression of tumorigenicity 2 protein (sST2) is associated with new-onset atrial fibrillation (NOAF) in patients diagnosed with coronary artery disease (CAD). However, the predictive value of sST2 in patients with acute ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI) has not been well studied. Methods A total of 580 patients with STEMI undergoing primary PCI were consecutively recruited between January 2021 and January 2023. These patients were then categorized into two groups: the NOAF group and the no NOAF groups based on the presence of NOAF during admission. The concentration of sST2 in blood samples was measured in all patients. The clinical data from the two groups were prospectively analyzed to investigate the predictive factors of NOAF in patients with STEMI undergoing primary PCI. Results A total of 41 (7.1%) patients developed NOAF. The presence of NOAF has been found to be associated with various factors, including age, diabetes mellitus, hypertension, the left atrial (LA) diameter, N-terminal pro-brain natriuretic peptide, C-reactive protein (CRP), sST2, a Killip class of ≥2, and a final TIMI flow grade of <3. After including multiple factors, it was observed that LA diameter, CRP, sST2, a Killip class of ≥2, and a final TIMI flow grade of <3 remained significant risk factors for developing NOAF. The receiver operating characteristic (ROC) curve showed the following findings: (1) when the LA diameter exceeded 38.5 mm, the sensitivity and specificity values were observed to be 67.2% and 68.2%, respectively, and the area under the ROC curve (AUC) was 0.683 [95% confidence interval (CI): 0.545–0.732; p = 0.003]; (2) when the CRP level exceeded 8.59, the sensitivity and specificity values were observed to be 68.6% and 69.2%, respectively, and the AUC was 0.713 (95% CI: 0.621–0.778; p < 0.001); and (3) when the sST2 value exceeded 53.3, the sensitivity and specificity values were 79.2% and 68.7%, respectively, and the AUC was 0.799 (95% CI: 0.675–0.865; p < 0.001). Conclusion sST2 has been identified as an independent predictor of NOAF in patients with STEMI undergoing PCI.